2007
DOI: 10.1534/genetics.107.072652
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scan to Detect Genetic Structure and Adaptive Genes of Natural Populations of Cryptomeria japonica

Abstract: We investigated 29 natural populations of Cryptomeria japonica using 148 cleaved amplified polymorphic sequence markers to elucidate their genetic structure and identify candidate adaptive genes of this species. In accordance with the inferred evolutionary history of the species during and after the last glacial episode, the genetic diversity was higher in western populations than in northern populations. The results of phylogenetic and genetic structure analyses suggest that populations of the two main variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 46 publications
12
67
6
1
Order By: Relevance
“…The R s values also varied, from 1.569 to 1.794 with an average of 1.721, and the H e values ranged from 0.292 to 0.320 with an average of 0.311 (Table 2). In contrast to findings from previous studies, these parameters do not reveal any clear geographical trends (Takahashi et al, 2005;Tsumura et al, 2007). The average F IS value for all loci was not significantly different from expectations under the Hardy-Weinberg equilibrium except for one locus, SNPg04215.…”
Section: Genetic Structurecontrasting
confidence: 99%
See 3 more Smart Citations
“…The R s values also varied, from 1.569 to 1.794 with an average of 1.721, and the H e values ranged from 0.292 to 0.320 with an average of 0.311 (Table 2). In contrast to findings from previous studies, these parameters do not reveal any clear geographical trends (Takahashi et al, 2005;Tsumura et al, 2007). The average F IS value for all loci was not significantly different from expectations under the Hardy-Weinberg equilibrium except for one locus, SNPg04215.…”
Section: Genetic Structurecontrasting
confidence: 99%
“…Hierarchical analysis indicated that genetic variation among varieties and populations accounted for 2.74% and 4.98% of the total variation, respectively. These results are similar to those from our previous study (Tsumura et al, 2007). While there was little genetic differentiation between variety groups, what differentiation there was pertained to genes related for local adaptation.…”
Section: Genetic Structuresupporting
confidence: 91%
See 2 more Smart Citations
“…As a goal of this study, we assessed how 2 years of additional marker development would aVect the reliability of results collected with relatively few markers. Several genome scan studies have reanalysed existing data sets with diVerent outlier tests (Vitalis et al 2001;Beaumont and Balding 2004) or assessed the validity of outlier tests by using more than one test statistic (Vasemagi et al 2005;Kane and Rieseberg 2007;Tsumura et al 2007;Egan et al 2008;Mäkinen et al 2008). In contrast, extending a genome scan by doubling the number of markers has been done here for the Wrst time.…”
Section: Discussionmentioning
confidence: 99%